The role of academic health centres in improving health equity: a systematic review. Issue 2 (26th March 2018) - Edelman, Alexandra; Taylor, Judy; Ovseiko, Pavel V.; Topp, Stephanie M.
Abstract : Purpose: Academic health centres (AHCs) are organisations that pursue a "tripartite" mission to deliver high-quality care to patients, undertake clinical and laboratory research, and train future health professionals. The last decade has seen a global spread of AHC models and a growing interest in the role of AHCs in addressing health system equity. The purpose of this paper is to synthesise and critically appraise the evidence on the role of AHCs in improving health equity. Design/methodology/approach: Peer-reviewed and grey literature published in English between 2000 and 2016 were searched. Articles that identified AHCs as the primary unit of analysis and that also addressed health equity concepts in relation to the AHC's activity or role were included. Findings: In total, 103 publications met the inclusion criteria of which 80 per cent were expert opinion. Eight descriptive themes were identified through which health equity concepts in relation to AHCs were characterised, described and operationalised: population health, addressing health disparities, social determinants of health, community engagement, global health, health system reform, value-based and accountable financing models, and role clarification/recalibration. There was consensus that AHCs can and should address health disparities, but there is a lack of empirical evidence to show that AHCs have a capacity to contribute to health equity goals or are demonstrating this contribution. Originality/value: This review highlights the relevance of health equity concepts in discussions about the role and missions of AHCs. Future research should improve the quality of the evidence base by empirically examining health equity strategies and interventions of AHCs in multiple countries and contexts.